Cesarean section in the People’s Republic of China: current perspectives - Feng XL; Wang Y; An L; Ronsmans C (Dove Medical Press, 2014)
Xing Lin Feng,1 Ying Wang,1 Lin An,2 Carine Ronsmans3 1Department of Health Policy and Administration, School of Public Health, Peking University, Beijing, People’s Republic of China; 2Department of Women, Children and Adolescent Health, School of Public Health, Peking University, Beijing, People’s Republic of China; 3Department of Infectious Disease Epidemiology, London School of Hygiene and Tropical Medicine, London, England Objective: To review the current knowledge on the prevalence, reasons, and consequences of cesarean sections in the People’s Republic of China. Methods: Peer-reviewed articles were systematically searched on PubMed. The following Chinese databases were comprehensively searched: the China National Knowledge Infrastructure, Wanfang, and the VIP information. The databases were searched from inception to September 1, 2013. Two reviewers independently screened the titles and abstracts for eligibility. Full texts of eligible papers were reviewed, where relevant references were hand-searched and reviewed. Findings: Sixty articles were included from PubMed, 17 articles were intentionally picked out from Chinese journals, and five additional articles were added, for a total of 82 articles for the analysis. With a current national rate near 40%, the literature consistently reported a rapid rise of cesarean sections in the People’s Republic of China in the past decades, irrespective of where people lived or their socioeconomic standing. Nonclinical factors were considered as the main drivers fueling the rise of cesareans in the People’s Republic of China. There was a lively debate on whether women’s preferences or providers’ distorted financial incentives affected the rise in cesarean sections. However, recent evidence suggests that it might be the People’s Republic of China’s health development approach – focusing on specialized care and marginalizing primary care – that is playing a role. Although 30 articles were identified studying the consequences of cesareans, the methodologies are in general weak and the themes are out of focus. Conclusion: The overuse of cesareans is rising alarmingly in the People’s Republic of China and has become a real public health problem. No consensus has been made on the leverage factors that drive the cesarean epidemic, particularly for those nonclinical factors. The more macro level structural factors may have played a part, though further research is warranted to understand the mechanisms. Knowledge of the consequences of cesareans, particularly for women, is limited in the People’s Republic of China, leaving a substantial literature gap. Keywords: cesarean section, People’s Republic of China